Effects of nitrogen application on corn yield after harvesting the apical ear as baby corn - Silva,Paulo Sérgio L (2013)
Removal of the first female inflorescence in corn induces the plant to produce new inflorescences, which allows the first ear to be harvested as baby corn and the second to be harvested as green or mature ear (dry corn). The objective of this study was to compare the following production systems fertilized with nitrogen levels (0, 80, and 160 kg ha-1), applied to corn hybrid AG 1051: baby corn harvesting (BC); green ear harvesting (GC); mature ear harvesting (DC); and harvesting of the first female inflorescence as baby corn + harvesting the other ears as green corn (BC + GC) or as dry corn (BC + DC). A randomized complete block design with split-plots (nitrogen in plots) and nine replicates was used. The BC system provided higher baby corn yields than the BC + GC or the BC + DC systems. For all traits employed to evaluate green corn yield, the GC system provided higher yields than the BC + GC system. The BC + DC system provided lower grain yield than the DC system. The application of nitrogen provided increases in all traits evaluated, except for number of kernels ear-1 and 100-kernel weight. The revenue (total and additional total) and additional profit values, in descending order, were obtained with the BC, BC + GC, BC + DC, GC, and DC systems, for all nitrogen levels. The values for those measurements increased as nitrogen dose increased. At the dose of 80 kg N ha-1, the highest profitability index (percentage of additional revenue that is converted into additional profit) was obtained from DC sales. However, with the application of the highest nitrogen rate, the highest profitability was obtained from BC sales.